"Water dynamics in the soil‐plant‐atmosphere system" by J.T. Ritchie, Plant and Soil (1981) 58:81–96. Issue 2 (7th February 2020) - Sinclair, Thomas R.
Abstract: This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by J.T. Ritchie published in 1981 that explored the use of extractable soil water as an independent variable for defining plant response to water deficit conditions. Recognizing the difficulty of using leaf water potential in defining plant response, he proposed an independent variable based on volumetric soil water content. Specifically, plant response was based on extractable soil water described as a function of 'fraction of total extractable water in the root zone.' Ritchie proposed a template for sensitivity of plant processes to soil drying based on fraction of total extractable water. Response functions based on this template have now been extensively studied and are key parts of many approaches to describing water use in both experimental and modeling studies.